К вопросу об особенностях соотношения глиальных элементов в различных отделах коры головного мозга кролика - Гончаренко, Л.Е.; Жданова, М.В.; Квитницкая-Рыжова, Т.Ю. (Вестник зоологии, 1972)
Astrocytes, obligodendrogliocytes and microgliocytes are calculated in the cerebral cor-tex of frontal, parietal and occipital areas of six sound rabbits. It was established that in the mentioned areas oligodendrogliocytes predominate quantitatively, astorcytes occupy the second place, microgliocytes — the third one. Quantitative content of astrocytes and microglicocytes is relatively single-valued in all the investigated areas. The following ty¬pical peculiarity in distribution of oligodendrogliocytes is determined: in the occipital area cortex their number is twice as large as in the frontal area cortex. The latter should be¬taken into consideration when estimating progressive changes in glia that accompany many pathological processes (in cases of experiments with rabbits).